The Influence Of Development Human Resources Development And Work Motivation On Employee Performance At PT. Aerofood Indonesia Surabaya Branch - Maria Florentina Arjen; Achmad Sholihin (SEAN Institute, 2024)
The purpose of this study is to evaluate the relationship between work motivation and the development of my resources on employee performance. The general issue addressed is the need for businesses to enhance employee performance through effective human resource strategies and motivational techniques. The study was conducted on employees of PT. Aerofood Indonesia Surabaya Branch, using a survey method in the form of a questionnaire. The sample was calculated using the Slovin formula at a confidence level of 10%, resulting in 70 respondents. The research employed quantitative methods, and the analysis technique used was multiple regression analysis, conducted with SPSS software. The results indicate that both human resource development and work motivation significantly influence employee performance. The discussion highlights the importance of continuous professional development and motivational strategies in improving organizational productivity. Recommendations for future research and practical applications are also provided.